THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON COST OF EQUITY IN COMPANIES IN THE JAKARTA ISLAMIC INDEX (JII) INDONESIA STOCK EXCHANGE - Riska; Damirah; Semaun, Syahriyah (Institut Agama Islam Negeri Parepare, 2023)
Good corporate governance is important in maintaining the integrity and sustainability of the company, including in a sharia-based business environment. This research aims to find out how good Good Corporate Governance is at companies listed on the Jakarta Islamic Index (JII) and the effect of implementing Good Corporate Governance on the Cost of Equity during the 2020-2022 period in companies listed on JII. Quantitative research method with an associative research approach, namely field research (Filed Research) using documentation techniques in the form of secondary data, annual reports and historical data of companies listed on the JII Indonesia Stock Exchange. The results of the research show that the Good Corporate Governance implemented by companies on the Jakarta Islamic Index (JII) during the 2020-2022 period is included in the good category in the analysis of the company's annual report and the shares are suitable for investment. The results of the Pearson correlation coefficient test were obtained at 0.639 (63.9%) indicating a strong and positive relationship that was significant at the significance level or Sig. (2-tailed) 0.04 and the test results from the partial test (t) show that the significant value is 0.004 <0.05 or the Sig t value is smaller than 0.05 so it can be concluded that the Good Corporate Governance variable has an effect on the Cost of equity.